National Survey of Police Call Management Strategies and Community Policing Activities, 2000 - McEwen, J. Thomas ([Verlag nicht ermittelbar], 2004)
For this study, two different projects with an overlap of purpose made use of the same data, which were based on a national sample of 695 police departments. One project conducted background research for a guidebook on call management for community policing. The other focused on the use of computer-aided dispatch (CAD) systems in community policing. Survey questions focused on the types of CAD systems, call management strategies, and community policing activities employed by each of the departments. Variables include types of CAD data used, use of different call management strategies, problem solving measures used, resource allocation measures used, community involvement/satisfaction measures used, support for special units, methods used for management accountability, and involvement in community policing activities.